A vehicle-centric algorithm for hybrid route guidance - Farver, J.; Chabini, I. (SMC'03 Conference Proceedings. 2003 IEEE International Conference on Systems, Man and Cybernetics. Conference Theme - System Security and Assurance (Cat. No.03CH37483), 2003)
This paper presents a decentralized algorithm that can function as a component of a hybrid centralized/decentralized route guidance system. The focus of the algorithm's design is on vehicle-level communication and computation for the purpose of developing vehicle-centric route guidance. The algorithm has been implemented and tested on a sample network in which both guided and unguided vehicles are modeled. Results are given which show that the algorithm is successful at responding to small amounts of network stochasticity as well as to congestion caused by incidents.